2014
DOI: 10.4049/jimmunol.1400764
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 Activation Is Sufficient but Not Required for Inducing Human T-Lineage Specification

Abstract: Although the role for the individual Notch receptors in early hematopoiesis have been thoroughly investigated in mouse, studies in human have been mostly limited to the use of pan-Notch inhibitors. However, such studies in human are important to predict potential side effects of specific Notch receptor blocking reagents because these are currently being considered as therapeutic tools to treat various Notch-dependent diseases. In this study, we studied the individual roles of Notch1 and Notch3 in early human h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Most studies were mainly focused on CD34+ hematopoietic progenitors and DCs stage. For instance,Els Waegemans et al reported that blocking of Notch1 signaling at the stage of CD34+ hematopoietic progenitors resulted in a complete block in T-lineage specification and induced monocytic and plasmacytoid dendritic cells [ 21 ]. However, another study, which repealed that MicroRNA-23b promoted tolerogenic properties of dendritic cells in vitro through inhibiting Notch1/NF-jB signalling pathways, was mainly focus on the mature DC stage [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies were mainly focused on CD34+ hematopoietic progenitors and DCs stage. For instance,Els Waegemans et al reported that blocking of Notch1 signaling at the stage of CD34+ hematopoietic progenitors resulted in a complete block in T-lineage specification and induced monocytic and plasmacytoid dendritic cells [ 21 ]. However, another study, which repealed that MicroRNA-23b promoted tolerogenic properties of dendritic cells in vitro through inhibiting Notch1/NF-jB signalling pathways, was mainly focus on the mature DC stage [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In human, similar developmental stages of early T cell development exist, but the molecular processes that control them are less clear. While the requirement for strong NOTCH1 signalling to induce T-lineage specification is well-established 15 16 , studies from our lab and others have revealed some remarkable differences in how this pathway controls later stages of T cell development in human compared to in mouse, with strong Notch-dependent TCR-Ī³Ī“ development in human as the most remarkable difference 15 17 18 19 . However, these studies also revealed that Notch signalling is permissive for NK cell development 20 , indicating that Notch activation is not sufficient to induce T-cell commitment, in agreement with other studies 7 21 .…”
mentioning
confidence: 85%
“…Notch3 is expressed in the early stages of Tā€cell development, but it normally becomes downregulated as cells transition to the doubleā€positive stage during maturation. Furthermore, Notch3 appears to be redundant for Tā€cell development, whereas Notch1 is required . Even so, Notch3 expression is found in the majority of Tā€cell acute lymphoblastic leukemia (Tā€ALL) cases.…”
Section: Leukemiamentioning
confidence: 99%